2019
DOI: 10.1002/gch2.201900037
|View full text |Cite
|
Sign up to set email alerts
|

Facile Solution Processing of Stable MXene Dispersions towards Conductive Composite Fibers

Abstract: 2D transition metal carbides and nitrides called “MXene” are recent exciting additions to the 2D nanomaterials family. The high electrical conductivity, specific capacitance, and hydrophilic nature of MXenes rival many other 2D nanosheets and have made MXenes excellent candidates for diverse applications including energy storage, electromagnetic shielding, water purification, and photocatalysis. However, MXene nanosheets degrade relatively quickly in the presence of water and oxygen, imposing great processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 46 publications
(101 reference statements)
0
95
0
Order By: Relevance
“…Investigation using the dynamic light scattering (DLS) technique revealed that ≈78% of the MXene flakes in the as‐synthesized dispersion had an average size of ≈0.58 µm, while there were ≈6% of larger flakes with an average size of ≈5.21 µm; the average size of the remaining flakes was ≈0.12 µm (Figure S1c, Supporting Information). Since PU used in this work was insoluble in water, we used a solvent exchange method34 to transfer Ti 3 C 2 T x MXene aqueous dispersion into dimethyl sulfoxide (DMSO) and dimethyl formamide (DMF) to achieve solvent compatibility with PU. In our initial investigation on drop‐cast films, MXene/PU composite prepared in DMSO showed electrical conductivity at ≈10 wt% MXene, while the composite film cast from a DMF dispersion with the same loading of MXene was not electrically conductive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation using the dynamic light scattering (DLS) technique revealed that ≈78% of the MXene flakes in the as‐synthesized dispersion had an average size of ≈0.58 µm, while there were ≈6% of larger flakes with an average size of ≈5.21 µm; the average size of the remaining flakes was ≈0.12 µm (Figure S1c, Supporting Information). Since PU used in this work was insoluble in water, we used a solvent exchange method34 to transfer Ti 3 C 2 T x MXene aqueous dispersion into dimethyl sulfoxide (DMSO) and dimethyl formamide (DMF) to achieve solvent compatibility with PU. In our initial investigation on drop‐cast films, MXene/PU composite prepared in DMSO showed electrical conductivity at ≈10 wt% MXene, while the composite film cast from a DMF dispersion with the same loading of MXene was not electrically conductive.…”
Section: Resultsmentioning
confidence: 99%
“…The aqueous MXene dispersion was transferred into DMSO or DMF via a solvent exchange method34 using repeated centrifugation (Thermo Scientific Sorvall ST40) of the parent MXene dispersion at 9000 rpm for one hour. After each centrifugation step, the supernatant was removed and replaced with DMSO or DMF, and the sediment was redispersed using a vortex mixer and manual shaking.…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasonication is another simple and promising process to deconstruct bulk materials into small particles. This method has been widely used in the field of nanomaterials, especially in the redispersion of colloidal nanoparticles, such as the exfoliation of graphite into graphene 72 and the delamination of other 2D nanomaterials, such as MXenes [73][74][75] , and clay minerals, such as layered double hydroxides and layered transition metal oxides/hydroxides 76 .…”
Section: Ultrasonicationmentioning
confidence: 99%
“…To address this issue, the dispersibility of Ti 3 C 2 T x in organic solvents was studied using simple solvent exchange processes consisting of repeated centrifugation and manual shaking. [35,36] As shown in Figure 2b, polar solvents, like dimethylformamide (DMF) and dimethylsulfoxide (DMSO), were identified as better dispersing Ti 3 C 2 T x due to somewhat similar polar termination groups, although low concentration dispersions in many other solvents, such as ethanol, can be achieved with sonication and centrifugation. [35] Beyond dispersibility, understanding the stability of MXene in both aqueous and organic solvents is important for fiber processing and large-scale applications.…”
Section: Solvent Selection and Stabilitymentioning
confidence: 99%
“…Due to the good dispersibility of MXene in polar solvents, a large range of materials, e.g., PCL, [36] polyurethane (PU), [41] PEDOT:PSS ( Figure 3c-ii,iii), [99] and GO, [111,112] have been added as components to the spinning dope to produce MXene-based composite fibers. These spinnable materials significantly improved the processability of MXene flakes into fibers.…”
Section: Wet Spinningmentioning
confidence: 99%